2012
DOI: 10.1007/s11046-012-9575-2
|View full text |Cite
|
Sign up to set email alerts
|

Cryptococcus laurentii Biofilms: Structure, Development and Antifungal Drug Resistance

Abstract: A great number of fungal infections are related to biofilm formation on inert or biological surfaces, which are recalcitrant to most treatments and cause human mortality. Cryptococcus laurentii has been diagnosed as the aetiological pathogen able to cause human infections mainly in immunosuppressed patients and the spectrum of clinical manifestations ranges from skin lesions to fungaemia. The effect of temperature, pH and surface preconditioning on C. laurentii biofilm formation was determined by 2, 3-bis (2-m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
19
0
2

Year Published

2014
2014
2020
2020

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(21 citation statements)
references
References 40 publications
0
19
0
2
Order By: Relevance
“…Although C. neoformans and C. gattii forms hyphae in the course of mating, these structures have not been observed in cryptococcal biofilms which consist of yeast cells that shed capsular polysaccharide which contributes to the ECM organisation. It has been demonstrated that this structure is more resistant than planktonic cells to oxidative stress suggesting that this phenotype increases resistance against host immune mechanisms and antifungal drugs, phenomena that could contribute to persistent infections …”
Section: How Does the Infection Occur?mentioning
confidence: 99%
See 1 more Smart Citation
“…Although C. neoformans and C. gattii forms hyphae in the course of mating, these structures have not been observed in cryptococcal biofilms which consist of yeast cells that shed capsular polysaccharide which contributes to the ECM organisation. It has been demonstrated that this structure is more resistant than planktonic cells to oxidative stress suggesting that this phenotype increases resistance against host immune mechanisms and antifungal drugs, phenomena that could contribute to persistent infections …”
Section: How Does the Infection Occur?mentioning
confidence: 99%
“…It has been demonstrated that this structure is more resistant than planktonic cells to oxidative stress suggesting that this phenotype increases resistance against host immune mechanisms and antifungal drugs, phenomena that could contribute to persistent infections. [50][51][52][53] Extrapulmonary dissemination, mainly to the CNS, is invariably associated with disease. The basis of C. neoformans/C.…”
Section: The Causative Agent Of Cryptococcosismentioning
confidence: 99%
“…Previous studies have shown that these conditions also enhance planktonic and biofilm growth of other fungal species (Ajesh & Sreejith, 2012;Di Bonaventura et al, 2006). T. inkin biofilms were formed in either low-glucose media (CLED, RPMI) or a nutrient-rich medium (Sabouraud) at both pH 7.0 and 5.5.…”
mentioning
confidence: 99%
“…Approximately 80% of non-neoformans cryptococcal infections are caused by C. laurentii and Cryptococcus albidus [4]. Most cases of nonneoformans cryptococcal fungemia are nosocomially acquired and the presence of invasive devices is a significant predisposing factor particularly when associated with C. laurentii infections [6]. Although in the present case, the patient did not have any indwelling medical device (e.g., central venous line), by having a hematological…”
Section: Discussionmentioning
confidence: 58%